2018
DOI: 10.1016/j.jpor.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between missing tooth count and mortality: A systematic review

Abstract: Although high variability in the studies precludes a definite conclusion about the relationship between number of teeth and mortality, the overall finding from this review is that reduced tooth count is associated with higher mortality. However the impact of factors such as smoking, health-care access, baseline co-morbidity and risk profile, dental and periodontal health, the presence of dental prosthesis as well as socio-economic status, in mediating whole or part of the association cannot be overlooked and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
64
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 63 publications
4
64
1
Order By: Relevance
“…Third, tooth loss and denture use are closely related, but the potential interaction between tooth loss and denture use, in relation to mortality, have not been comprehensively evaluated. Forth, many important confounders, like economic status, were not adjusted in most previous studies [5][6][7][8][9][10][11][12][13]. Fifth, previous studies evaluating denture use and mortality showed inconsistent results [13,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, tooth loss and denture use are closely related, but the potential interaction between tooth loss and denture use, in relation to mortality, have not been comprehensively evaluated. Forth, many important confounders, like economic status, were not adjusted in most previous studies [5][6][7][8][9][10][11][12][13]. Fifth, previous studies evaluating denture use and mortality showed inconsistent results [13,21].…”
Section: Introductionmentioning
confidence: 99%
“…A number of prospective studies have found an association between tooth loss and all-cause mortality, cardiovascular and cancer mortality [5][6][7][8][9][10][11]. Wearing dentures may reduce the mortality in older adults [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Tooth loss can also impact facial appearance and therefore affect self‐esteem and socialization . Other systemic conditions, such as cognitive decline and peripheral arterial disease, as well as overall mortality, have been linked to tooth loss. Financial limitations have also been linked to reduced oral healthcare utilization among older adults in multiple countries, and increased oral health insurance coverage is associated with higher use of oral healthcare services …”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have reported tooth loss and complete edentulism to be associated with multiple systematic comorbid conditions such as obesity, COPD‐related events, pneumonia, head and neck cancer, and cognitive decline as well as with an increased risk of mortality . Gupta and Koka conducted a systematic review to examine the association between tooth count and all types of mortality and found an overall trend towards a relationship between the number of teeth and mortality, with a lower tooth count being associated with higher all‐cause and cause‐specific mortality . Furthermore, Osterberg et al showed tooth loss to be an independent risk factor for increased mortality in 70‐year‐old patients, irrespective of socioeconomic or lifestyle factors .…”
mentioning
confidence: 99%